Analysis of Liver Fibrosis Degree with APRI Score and FIB-4 Index on Patients with Non-Alcoholic Fatty Liver Disease - Gillian Elvira Seipalla; Nurahmi Nurahmi; Ibrahim Abd Samad (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Liver fibrosis is the accumulation of Extracellular Matrix Protein (EMP) scar tissue after acute or chronic liver injury. Liverbiopsy is the gold standard test for evaluating liver fibrosis in patients with Non-Alcoholic Fatty Liver Disease (NAFLD). Thisdiagnostic method is invasive, painful, and complicated in rare cases; thus the noninvasive methods such as laboratory testsand radiology had been proposed to assess liver fibrosis in NAFLD and are expected to overcome the limitations of liverbiopsy. This method consists of aspartate Aminotransferase to the Platelet Ratio Index (APRI) and fibrosis-4 (FIB-4).Thisresearch was retrospective cross-sectional performed at Dr. Wahidin Sudirohusodo Hospital Makassar involving 63 subjectsfrom January to June 2018. The correlated variables were presented in categorical and numerical data and the Pearsoncorrelation test was used to determine the compatibility of APRI score and FIB-4 index with Fibroscan result in patientswith NAFLD. A highly significant positive correlation (p <0.001) was found between APRI score and Fibroscan (correlationvalue = 45.8%), APRI score and FIB-4 index (correlation value = 91.8%), FIB-4 index and Fibroscan (correlationvalue = 47.6%). The score of Aminotransferase to platelet ratio index score and FIB-4 index could be an alternative methodinstead of a liver biopsy to predict the degree of fibrosis in patients with NAFLD.